Knowledge and Civil Society - Glückler, Johannes; Meyer, Heinz-Dieter; Suarsana, Laura (Knowledge and Space, 2022)
This open access book focuses on the role of civil society in the creation, dissemination, and interpretation of knowledge in geographical contexts. It offers original, interdisciplinary and counterintuitive perspectives on civil society. The book includes reflections on civil and uncivil society, the role of civil society as a change agent, and on civil society perspectives of undone science. Conceptual approaches go beyond the tripartite division of public, private and civic sectors to propose new frameworks of civic networks and philanthropic fields, which take an inclusive view of the connectivity of civic agency across sectors. This includes relational analyses of epistemic power in civic knowledge networks as well as of regional giving and philanthropy. The original empirical case studies examine traditional forms of civic engagement, such as the German landwomen's associations, as well as novel types of organizations, such as giving circles and time banks in their geographical context. The book also offers insider reflections on doing civil society, such as the cases of the Umbrella Movement in Hong Kong, epistemic activism in the United States, and the #FeesMustFall movement in South Africa.